2017
DOI: 10.3354/dao03132
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and antimicrobial resistance genes of Yersinia ruckeri isolates from rainbow trout farms

Abstract: In this study, we compared 142 Yersinia ruckeri isolates collected between 2013 and 2016 from 6 different regions in Turkey. A total of 18 different genogroups were found, though most of the isolates clustered into the same genogroup as serotype O1. As immunization of fish with inactivated Y. ruckeri by injection, immersion, or feeding provide minimal protection against Y. ruckeri infection in Turkey, many fish producers use antimicrobials unrestrictedly, resulting in antimicrobial resistance in aquatic pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Histological examination showed necrosis of exocrine pancreatic tissue, and sometimes fat cells had replaced pancreatic cells (data not shown). Flavobacterium psycrophilum was frequently isolated, while Lactococcus garvieae and Yersinia ruckeri (Duman et al., ) were observed less frequently (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Histological examination showed necrosis of exocrine pancreatic tissue, and sometimes fat cells had replaced pancreatic cells (data not shown). Flavobacterium psycrophilum was frequently isolated, while Lactococcus garvieae and Yersinia ruckeri (Duman et al., ) were observed less frequently (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…A. salmonicida (A5) isolated from dorsal lesions of broodstock rainbow trout (3,000 g) was combined with Y. ruckeri and IPNV. Considering that Y. ruckeri has caused disease particularly in 12–15°C water temperatures (Austin & Austin, ; Duman, Altun et al., ), we can speculate that A. salmonicida causes disease in broodstock. Moreover, the A5 isolate is the most distinct phylogroup of all Aeromonas species; hence, this isolate should be used for a detailed genetic analysis.…”
Section: Discussionmentioning
confidence: 92%
“…( E. cloacae, M. psychrotolerans and Flavobacterium articles in process). (Table ; Büyükekiz et al., ; Duman, Altun et al., ; Duman, Saticioglu et al., ; Duman, Buyukekiz et al., ). In some cases, only A. sobria, A. media, A. bestiarum and A. salmonicida isolates were seen as primary infectious agents in rainbow trout showing dorsal lesions and from water temperatures between 9.5 and 19.1°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recovering of agent from different region revealed that Y. ruckeri has a high spreading potentially between aquaculture. Y. ruckeri isolates were reported as biochemically hetero-genic according to the different isolation source and also determined as four different group by outer membrane protein profiles and isolates have 86,03% similarities between each other (Altınok et al, 2016;Duman et al, 2017a). Altun et al, (2013a) reported that there were many biochemical differences, and also 17 Y. ruckeri isolates were diverged as five genotype by working on phenotypic and biochemical studies.…”
Section: Introductionmentioning
confidence: 99%